2020
DOI: 10.3390/ma13092066
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration Characteristics of Discrete Fragments Generated from Explosively-Driven Cylindrical Metal Shells

Abstract: The acceleration characteristics of fragments generated from explosively-driven cylindrical shells are important issues in warhead design. However, there is as yet no reasonable theory for predicting the acceleration process of a specific metallic shell; existing approaches either ignore the effects of shell disintegration and the subsequent gas leakage on fragment acceleration or treat them in a simplified manner. In this paper, a theoretical model was established to study the acceleration of discrete fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Results confirm that the formula developed with a numerical model could accurately predict fragment speed dispersion along the axis and circumference of the cylindrical skin under an eccentric start point at one end, thereby simulating the edge effect. Further, Studies reported calculating the fragment velocity of hollow-core warheads with asymmetric detonation [31][32][33][34] . Recently, Jifeng Wei et.al 35 studied the fragmentation of a thinwalled Q235 steel shell under an explosion of TNT.…”
Section: Introductionmentioning
confidence: 99%
“…Results confirm that the formula developed with a numerical model could accurately predict fragment speed dispersion along the axis and circumference of the cylindrical skin under an eccentric start point at one end, thereby simulating the edge effect. Further, Studies reported calculating the fragment velocity of hollow-core warheads with asymmetric detonation [31][32][33][34] . Recently, Jifeng Wei et.al 35 studied the fragmentation of a thinwalled Q235 steel shell under an explosion of TNT.…”
Section: Introductionmentioning
confidence: 99%